Rural development perspectives in enlarging Europe: The implications of CAP reforms and agricultural transition in accession countries - Marian Rizov (European Planning Studies, 2006)
The purpose of this paper is to put into an appropriate theoretical frame the rural development issues in enlarging Europe and to analyse the rural development perspectives in the European Union (EU) accession countries. Based on comparisons of developments in the Common Agricultural Policy (CAP) and features of the rural areas in incumbent EU member states with the status of the rural sectors in accession countries, implications for the future of CAP are discussed. It is argued that despite coming from different development doctrines, the dominant rural sector-agriculture-in both eastern and western Europe is similarly characterized by dual structure. Thus, emphasis on rural development structural policies currently being promoted by the reforming CAP can be fruitful in both new and incumbent member states.
Keywords: Q18; Q15; Q38; R11; R58; 330; Rural development; Transition; European CAP; Agrarian change; Accession; Agriculture